An Analysis of the Security Perspectives of the China-Pakistan Economic Corridor - Shaikh , Irfan Ahmed; Arain, Rehana Kausar; Khatti, Deedar Hussain; Rasool, Ghulam (Pakistan Journal of Humanities and Social Sciences, 2025)
The Ocean domain is the main sector of marine protection. It is a miscellaneous variety that encloses a host of marine elements ranging from pollution at the seas, vessel safety, regulation of marine boundary, search and rescue, maritime health, and the climate change and its impact on water bodies. This paper investigates the consequences of the giant influence of the feud in the Indian Ocean on the CPEC's sea security. The triumphant commission of this scheme bears immense consequence for Pakistan's birth of a new era for economic prospects. The China-Pakistan Economic Corridor underpins the mega project of the Belt and Road Initiative (BRI), whereby the Pakistan Navy has a central position in dispelling these rooted hazards. Similarly, it has a key part in varying anomalous perils like sea and ocean terrorism, separatism, human and drug trafficking, unlawful fishing, and protecting the oceanic resources of Pakistan. It has a huge role in growing the "blue economy" and contributes to the greater socioeconomic maturation of Pakistan. Ultimately, water diplomacy is the novel possible spot where the Navy resolves confrontations and fosters regional connectivity. This study collects secondary data via reliable document sources including journals and published research papers, which play a vital role in basing the data and investigation for this study. Likewise, the project CPEC poses many regional tensions, non-traditional challenges, and security protection in the form of terrorism, separatism, drug and human trafficking, and illegal fishery. These outcomes and future possibilities of the CPEC have enriched the activeness of Pakistan's navy into power.